Individualized antithrombotic therapy in high risk patients after coronary stenting. A double-edged sword between thrombosis and bleeding - May, Andreas E.; Geisler, Tobias; Gawaz, Meinrad (Thrombosis and Haemostasis, 2008)
Dual antiplatelet therapy with aspirin and clopidogrel is currently the standard therapy after coronary stent implantation to prevent a life-threatening stent thrombosis. However, a variety of procedural and individual factors contribute to the individual patient risk and have to be taken into account to allow for an individual recommendation for both the duration and intensity of the antiplatelet therapy. Obviously, the benefit of the prevention of stent thrombosis by antithrombotic therapy has to outweigh the risk of severe bleeding complications. Depending on the individual clinical situation and procedural characteristics (stent type, length, angiographic result etc.), the recommended duration of the combined antiplatelet therapy currently varies from four weeks to at least one year.These recommendations are mainly based on large, prospective, randomized trials and evidence-based guidelines. However, in a subgroup of high-risk patients there is insufficient evidence for the benefit of conventional dual antiplatelet regimen.These include i) patients with an indication for anticoagulation, ii) patients with urgent need for an operation requiring a perioperative withholding of antiplatelet therapy, as well as iii) clopidogrel low responders.This review aims to provide a stratification to define patient collectives who may benefit from more individualized antithrombotic regimens on behalf of currently available literature and guidelines.
Keywords: Antiplatelet agents; antiplatelet drugs; clinical trials; atherothrombosis; atherosclerosis; acute myocardial infarction